Practical Acoustic Emission Testing - The Japanese Society for Non-Destructive (Springer Japan : Imprint: Springer, 2016)
This book is intended for non-destructive testing (NDT) technicians who want to learn practical acoustic emission testing based on level 1 of ISO 9712 (Non-destructive testing - Qualification and certification of personnel) criteria. The essential aspects of ISO/DIS 18436-6 (Condition monitoring and diagnostics of machines - Requirements for training and certification of personnel, Part 6: Acoustic Emission) are explained, and readers can deepen their understanding with the help of practice exercises. This work presents the guiding principles of acoustic emission measurement, signal processing, algorithms for source location, measurement devices, applicability of testing methods, and measurement cases to support not only researchers in this field but also and especially NDT technicians.